Model Pembelajaran Daring Pada Mata Pelajaran IPS Masa Pandemi Covid- 19 di SMP Negeri 2 Girsang Sipangan Bolon Semester Genap T.A 2020/2021 - Marudut Hasanuddin Panggabean; Corry Corry; Tuangkus Harianja; Ease Arent; Rima Melatih (Departement of Mathematics Education, 2023)
Abstract. Abstract. This study aims to analyze how the Online Learning Model for social studies subjects is applied at SMP Negeri 2 Girsang Sipangan Bolon, Simalungun Regency during the Covid-19 Pandemic Period, Even Semester Academic Year 2020/2021. This study uses a qualitative descriptive method with case studies that are focused on clearly seeing how the online learning model is in Social Studies Subjects during the Covid-19 Pandemic at SMP Negeri 2 Girsang Sipangan Bolon. Data collection techniques are observation, interviews, and documentation. Interviews were conducted with the Principal, Vice Principal, Teachers and Students of SMP Negeri 2 Girsang Sipangan Bolon. The results of the study show that the Online Learning Model for Social Studies subjects at SMP Negeri 2 Girsang Sipangan Bolon during the Covid-19 Pandemic in general or 90% was carried out via the WAG application (WhatsApp Group) with all limitations ranging from gadget ownership, internet network, speed, flexibility, quota, signal, place of residence and parents so that the learning process becomes less effective.